PENCIPTAAN LOYALITAS PENGUNJUNG MELALUI EXPERIENTIAL MARKETING PADA BANDINI KOFFIEDI KOTA MATARAM - Mourris Sagara (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This research is aimed at determining the impelementation of creating  loyalties of visitor through experiential marketing in Bandini Koffie in Mataram. Tis research is qualitative study with 7 visitors as the respondents. The data were collected through indepth interview, observation, and documentatiion.The research showed that dimension of “feel” is resulting in the sense of comfortable state and happiness in the inner of visitors in this case in Bandini Koffie, and therefore this will create the loyalty of visitor. The dimension of “sense” is resulting in the experience for the visitors in seeing, listening, tasting, touching that all are stimulating the the sense of beauty and satisfaction in Bandini Koffie. The dimension of ‘think’ is resulting in creative thought of visitors about the different places in the mind  of visitors and therefore the visitor are driven to a certain trade mark of Bandini Koffie. The dimension of “act”  is an action of marketing to give a good service that is resulting the closeness between Bandini Koffie and the visitors. The dimension of “relate” is acombination of each dimension to create the happiness, satisfaction, and good feedback of visitors to Bandini Koffie. The five experiential marketing affect the localty of visitors of Bandini Koffie in  Mataram. Keyword : Customer Loyalty & Experiential Marketing